Ekovaina para el diseñó de empaques de exportación. (2020)
The project consists of the design and development of a specialized packaging system for the transport and display of export fruits based on the recovery of fiber derived from pea pods that are discarded in the market places. A potential with pea waste is identified since it has properties that can be used for the manufacture of multiple products, whether artisanal or industrially, such as in the manufacture of furniture, chipboard, acoustic panels, agricultural products, consumer products fast, packaging among others. The large amount of discarded and unused material and an exposed problem make the project great potential. From the Industrial Design we want to implement this material strategically, the design will play an important role since it is the means to extract the potential of the material, in a friendly way to the user and the environment, taking into account the contexts raised, the result is a focus on the design of packaging for export fruits. Additionally, this project is oriented to the use of new materials to contribute to the disuse of unnecessary plastic materials and, on the contrary, to promote the development of new sustainable and environmentally friendly alternatives.